Fly ash based geopolymer concrete with ferrochrome slag aggregates - Indu, P.; Greeshma, S.; Bedi, P. Kiran (Journal of Structural Engineering, 2024)
The technology of Geopolymer Concrete (GPC) is gaining importance in the present era because of the reducedcarbon dioxide emission and low embodied energy, when compared with the conventional cement concrete. GPC isobtained by the activation of silica and alumina rich source materials in the presence of alkali activator. This paperevaluates the strength and durability characteristics of fly ash based GPC with ferrochrome slag aggregates. The fineand coarse aggregates in the GPC were replaced with ferrochrome slag in various proportions, and it was noted thatthe coarse aggregate replacement performed better than the replacement of fine aggregates. The optimum replacementpercentage that gives the maximum strength in terms of coarse aggregate replacement was arrived at. The resultconcluded that the incorporation of ferrochrome slag as coarse aggregate at optimum level enhanced the strengthcharacteristics in comparison with the conventional GPC with normal aggregates. The durability characteristics ofthe various replacement mix was carried out, and the results of the optimum replacement mix was compared with theconventional geopolymer mix. Apart from these, the feasibility of utilising ferrochrome slag as aggregates in concretewere also ascertained by leaching tests.